Comparing the effect of rosemary and mefenamic acid capsules on duration of primary dysmenorrhea - Fahimeh Tahoonian Golkhatmy; Zahra Abedian; Seyed Ahmad Emami; Habibollah Esmaily (Mashhad University of Medical Sciences, 2017)
Introduction: Primary dysmenorrhea is one of the most common problems of women that its treatment is using non-steroidal anti-inflammatory drugs, but due to many complications are not acceptable. Considering analgesic and anti-inflammatory properties of rosemary, this study was performed with aim to compare the effects of rosemary and Mefenamic Acid capsules on the duration of primary dysmenorrhea. Methods: This double-blind clinical trial was performed on 90 students with primary dysmenorrhea in the School of Medicine, Islamic Azad University of Mashhad in 2016. To assess the pain intensity, VAS and duration of pain based on minutes were used. Research units were randomly assigned into two groups of 45 cases. One group received rosemary capsules 250 mg and the other group 250 mg Mefenamic Acid capsules during two cycles at first three days of menstruation every 8 hours. Data was analyzed by SPSS software (version 24) and Wilcoxon test, Mann-Whitney statistical tests. P<<0.05 was considered significant. Results: Mean duration of pain in rosemary group in the control cycle from 131.49±18.52 minutes decreased to 95.83±18.43 and 83.76±10.33 minutes, respectively in the first and second cycle of the intervention, and in Mefenamic Acid group in the control cycle from 182.12±28.59 minutes decreased to 140./16±30.07 and 130.04±26.44 minutes, respectively in the first and second cycle of the intervention. There was no significant difference between the two groups in the first and second cycles of intervention (p >0.05). Conclusion: Rosemary capsule is effective in reducing the duration of pain in primary dysmenorrhea and this plant can be used as a treatment method.